Place cells in the claustrum remap under NMDA receptor control. (17th June 2022) - Rizzello, Emanuela; Martin, Seán K.; Rouine, Jennifer; Callaghan, Charlotte; Mathiasen, Mathias L.; O'Mara, Shane M.
Abstract: Place cells are cells that exhibit location‐dependent responses; they have mostly been studied in the hippocampus. Place cells have also been reported in the rat claustrum, an underexplored paracortical region with extensive corto‐cortical connectivity. It has been hypothesised that claustral neuronal responses are anchored to cortical visual inputs. We show rat claustral place cells remap when visual inputs are eliminated from the environment, and that this remapping is NMDA‐receptor‐dependent. Eliminating visual input decreases claustral delta‐band oscillatory activity, increases theta‐band oscillatory activity, and increases simultaneously recorded visual cortical activity. We conclude that, like the hippocampus, claustral place field remapping might be mediated by NMDA receptor activity, and is modulated by visual cortical inputs. Abstract : Claustral place cells were recorded during light manipulation while rats navigated in a square arena; cell positions were estimated by histological analyses. Claustral place cells exhibit light‐dependent location‐specific responses. This remapping is NMDA‐receptor‐dependent.